Thermal disorder prevents the suppression of ultra-fast photochemistry in the strong light-matter coupling regime - Dutta, Arpan; Tiainen, Ville; Sokolovskii, Ilia; Duarte, Luís; Markešević, Nemanja; Morozov, Dmitry; Qureshi, Hassan A.; Pikker, Siim; Groenhof, Gerrit; Toppari, J. Jussi (Nature communications, 2024)
Strong coupling between molecules and confined light modes of optical cavities to form polaritons can alter photochemistry, but the origin of this effect remains largely unknown. While theoretical models suggest a suppression of photochemistry due to the formation of new polaritonic potential energy surfaces, many of these models do not account for the energetic disorder among the molecules, which is unavoidable at ambient conditions. Here, we combine simulations and experiments to show that for an ultra-fast photochemical reaction such thermal disorder prevents the modification of the potential energy surface and that suppression is due to radiative decay of the lossy cavity modes. We also show that the excitation spectrum under strong coupling is a product of the excitation spectrum of the bare molecules and the absorption spectrum of the molecule-cavity system, suggesting that polaritons can act as gateways for channeling an excitation into a molecule, which then reacts normally. Our results therefore imply that strong coupling provides a means to tune the action spectrum of a molecule, rather than to change the reaction. The aim of polaritonic chemistry is to control photochemical reactions by placing molecules inside optical cavities. Here, the authors show that this is not directly possible due to thermal disorder, which is unavoidable in real experiments, and polaritons mostly channel molecular excitations.